Pembelajaran Daring IPS Berbasis Google Classroom pada Masa Wabah Covid-19 kelas IX SMP Negeri 2 Kalimanah - Nur Said Manfaluti (UM Purwokerto Press, 2021)
The google classroom application is one of the most preferred learning management system applications in the Purbalingga District education unit for learning during the Covid-19 outbreak because it is easy to use. The purpose of this research is to find out 1) student responses in easy access to the Google classroom application, 2) understanding of the material in learning using google classroom, 3) the effectiveness of using the google classroom application in online learning, 4) The use of google classroom in learning evaluation. This research method uses descriptive research methods using survey techniques. The research instruments used were questionnaires and online interviews which were given to 256 students of class IX in the odd semester of the 2020/2021 school year. The results showed that as many as 52.93% of students stated that they disagreed with the ease of accessing the google classroom application, 62.63% of students agreed in understanding the learning material using google classroom, 60.42% of students agreed to the effectiveness of using the google classroom application, and 46.74% of students agreed to use the google classroom application in learning evaluation. It can be concluded that the use of the google classroom application in online learning during the Covid-19 outbreak was quite good and effective, it's just that it would be better if combined with other online platforms.